Performance Assessment of Organic Fibre-Reinforced Ceiling Boards for Sustainable Building Applications - Oloyede, Theophilus Olukunle; Abutu, Joseph; Mshelia, Zaka Audua (ABUAD Journal of Engineering Research and Development (AJERD), 2025)
This study developed two separate ceiling boards using snot apple fibre and cow hair with coconut shells and epoxy resin binder added in each of the boards in order to produce sustainable, lightweight, and cost-effective ceiling boards from agricultural and animal waste fibres as eco-friendly alternatives to conventional, non-renewable building materials. Natural fibres from plant and animal wastes were treated with sodium hydroxide and characterized by X-ray fluorescence, revealing distinct elemental compositions: coconut shell fibre rich in MgO (33.318%) and SiO₂ (20.044%), cow hair fibre high in SO₃ (54.35%), and snot apple fibre rich in MgO (38.006%) and SiO₂ (21.409%). Composite samples were produced via compression moulding using a Taguchi L9(3)3 design to vary filler, additive, and binder content systematically. Mechanical properties (tensile strength, hardness, impact energy), water absorption, thickness swelling, and microstructure were evaluated. Snot apple fibre-based boards (SAF) showed superior tensile strength (12.51MPa), hardness (79.5HVN), and impact energy compared to cow hair fibre boards (CHF) shows 9.29MPa tensile strength, 73.3HVN hardness, though with greater variability and thickness swelling. ANOVA revealed filler content primarily influenced cow hair boards’ tensile strength and hardness, while coconut shell and binder content were key for snot apple boards. Epoxy resin significantly affected water absorption and swelling in both, necessitating tailored formulations. SEM analysis performed on the optimised samples confirmed microstructural features correlating with performance while thermogravimetric analysis revealed that SAF ceiling boards demonstrates significantly superior thermal stability compared to the CHF composite, making it more suitable for high-temperature applications. Overall, the composites are suitable eco-friendly alternatives for ceiling board applications in building.